IMPACT OF SUPPLEMENTING DIETS WITH CHITOSAN AND PROBIOTICS ON CERTAIN BLOOD PROPERTIES OF BROILERS - W. I. Al-Jugifi; H. H. Nafea; N. N. Alhayani (مجلة الأنبار للعلوم الزراعية)
This experiment was conducted at the poultry farm of the Animal Production Department, College of Agriculture, University of Anbar from 28 December 2023 to 8 February 2024 (42 days). It aimed to compare the effect of adding two different levels of chitosan and probiotics to the diet and their combinations in the physiological performance and some blood characteristics of broilers from the age of 6 weeks. The study used 10 one-day-old Ross chicks of 40 g average weight. The chicks were distributed into 7 treatments of 3 replicates each (10 chicks for each replicate). The first treatment (T1) was the control (without any addition), the T2 and T3 treatments included adding chitosan at 1 and 2 g/kg feed, respectively. The T4 and T5 treatments included adding probiotic at 1 and 2 g/kg of feed, respectively. The T6 treatment included the addition of chitosan and probiotics at 0.5 g/kg of feed each while T7 included the addition of chitosan and probiotics at 1 g/kg feed each. Results show that the T5 treatment had significant superiority (P≤0.05) in the PCV and hemoglobin values compared to T1, T2, and T4, and did not differ significantly from the other treatments. Treatment T5 also continued to be superior in the number of red blood cells compared to T1, T2, T3, and T4 and did not differ significantly from the other treatments. There was also a significant decrease (P≤0.05) in the concentration of blood plasma glucose in T2 compared to T6, while treatment T2 recorded a significant increase in total protein concentration over T3, T4, and T6. Also, treatment T2 showed a significant increase in globulin concentration compared to T3 and T4 but was not significantly different from the other treatments. Lipid profiles recorded a significant decrease (P≤0.05) in the concentration of blood plasma cholesterol and low-density lipoproteins in treatment T6 compared to T2 and T4, but were not significantly different from the other treatments. Liver enzymes recorded a significant decrease (P≤0.05) in the AST enzyme level in treatment T2 over T4 and T5, but was not significantly at variance from the other treatments